Observation of the double Dalitz decay η′ → e+ e− e+ e− - Ablikim, M.; Achasov, M. N.; Adlarson, P.; Chelkov, G. A. (Physical Review D)
Based on (0087 +/- 44) x 10(6) J/psi events collected with the BESIII detector at BEPCII, the double Dalitz decay eta' -> e(+)e(-)e(+)e(-) is observed for the first time via the J/psi -> gamma eta' decay process. The significance is found to be 5.7s with systematic uncertainties taken into consideration. Its branching fraction is determined to be B(eta' -> e(+)e(-)e(+)e(-)) = (4.5 +/- 1.0(stat) +/- 0.5(sys)) x 10(-6).